Think like a horse : lessons in life, leadership, and empathy from an unconventional cowboy - Golliher, Grant; Daly, Ellen (G. P. Putnam's Sons, 2022)
Grant Golliher is what some would call a "horse whisperer," able to get a wild horse to calmly accept a saddle and a rider without the use of force. Through training thousands of horses, many traumatized or abused, Golliher was able to learn essential lessons about communication, boundaries, fairness, trust, and respect--lessons that apply not just to horses but to humans as well. It's why celebrities, Fortune 500 executives, professional coaches, supreme court justices, and even ordinary families from around the world flock to his Wyoming ranch every year to take part in what one CEO called "the most transformational experience I have ever encountered. Horse whispering may sound like magic, but as Grant explains in Think Like a Horse, it's not really all that mysterious. The lessons he shares are as fundamental and ageless as the relationship between horses, the people who ride them, and the beauty of the West. In fact, it's an approach that anyone can learn, and should learn, in order to better understand our common humanity, overcome trauma, foster more fulfilled relationships, and unlock untapped potential in virtually every aspect of our lives. All you have to do is think like a horse.--